Synthesis of Green Chitosan – Silver Nanoparticle Composite Material: Parameter Optimization and Physicochemical Characterization - Y, Tran Thi Nhu; Thien, Do Truong; Cong, Trinh Duc; Nu, Tran Thi; Thuy, Lai Thi; Thuc, Nguyen Thi; Tuan, Le Quang; Dat, Nguyen Dang; Hileuskaya, Kseniya; Kalatskaja, Joanna; Kulikouskaya, Viktoryia (VNU Journal of Science: Natural Sciences and Technology; Vol 38 No 4DO - 10.25073/2588-1140/vnunst.5363, 2022)
In this study, response surface methodology (RSM) was carried out with four parameters: chitosan concentration, AgNO 3 concentration, ascorbic acid concentration and time with the objective to obtain minimum mean particle size of silver nanoparticles (response Y). The chitosan-silver nanoparticle composite material (CTS-AgNPs nanocomposite) obtained experimentally from the optimal conditions was characterized by evaluating some of their physical-chemical properties using combined technique including visible ultraviolet spectroscopy (UV -Vis), dynamic light scattering (DLS), transmission electron microscopy (TEM), infrared spectra (IR) and X-ray diffraction. The optimal conditions were chitosan concentration of 19.2 %, silver nitrate of 26 mM, ascorbic concentration of 33 mM and time of 4.25 hours. Spherical Ag particles obtained experimentally were well dispersed in chitosan matrix with the average diameter of around 2÷8 nm with a narrow size distribution and homogeneous dispersion